A DEVELOPMENT LEARNING MEDIA APPLICATION OF SNAKES ON THE NERVOUS SYSTEM MATERIALS TO INCREASE LEARNING OUTCOMES AND CONCEPTS MASTERY OF HIGH SCHOOL STUDENTS IN THE 2020/2021 ACADEMIC YEAR - Andreansyah Andreansyah; Herliani Herliani; PM Labulan PM Labulan (Program Pascasarjana Universitas Negeri Jakarta, 2021)
The purpose of this study was to examine the validity, practicality, and effectiveness of the snake and ladder application